2005
DOI: 10.1063/1.2041843
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Al doping on the thermoelectric performance of CoSi single crystal

Abstract: Thermoelectric properties of heavily GaP-and P-doped Si 0.95 Ge 0.05

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…2 (b)]. We find that 4% Al substitution is the critical point that induces a sign change of S from negative to positive, again agreeing well with experiments [54,55]. At high Al concentration (>10%) the calculated S is about one half of the experimental values [54,55].…”
Section: B Seebeck Coefficient Resistivity and Power Factorsupporting
confidence: 86%
“…2 (b)]. We find that 4% Al substitution is the critical point that induces a sign change of S from negative to positive, again agreeing well with experiments [54,55]. At high Al concentration (>10%) the calculated S is about one half of the experimental values [54,55].…”
Section: B Seebeck Coefficient Resistivity and Power Factorsupporting
confidence: 86%
“…Here again, firstly starting from κ 0 behaviour at the µ corresponding to EF . It is seen to show an increasing behaviour similar to the one reported by Jian et al and Li et al for κe [32,37]. From the figure, it is found that, at the EF , the value of κ 0 is ∼ 2.4 x 10 14 Wm −1 K −1 s −1 at 300 K, where 10 14 is the order of τ .…”
Section: Thermal Conductivity (Electronic)supporting
confidence: 82%
“…One of the way through which this can be achieved is by doping of the material. As being one of the prime candidates for advanced thermoelectric applications, many investigations have already been done in order to improve its thermoelectric power, mostly by doping [8,12,[32][33][34][35][36][37]. It has been reported in these studies that transport coefficients of CoSi could be explained by using semi-metallic band structure model [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Later, there were several attempts with different dopants and alloys. The effects of Al substitution for Si on the thermoelectric performance of CoSi were investigated in the temperature range from 300 to 973 K . The solubility limit of Al in CoSi 1− x Al x is found to be in the range of x = 0.20–0.30.…”
Section: Cobalt Monosilicide Cosimentioning
confidence: 99%